The Flexibility Debate in Western Europe: The Current Drive to Restore Managements' Rights Over Personnel and Wages - Barkin, Solomon (Relations industrielles / Industrial Relations, 1987)
Managements' drive for the removal of contractual and govemmental restraints on their control of the work force is rationalized in Western Europe as necessary to achieve greater internal and external competitiveness. In support of this view the OECD substituted the advocacy of a flexible manpower policy (including wage policy) under the euphorie title of 'positive adjustment policy' for the prior program of an active manpower policy promoted during the sixties and early seventies. The soundness of the arguments for this change in policy has been questioned by internal research findings as well as reports by consultants and special expert groups appointed by the organization. These studies call for a package of policies and measures negotiated between management and unions to realize the ultimate ends of manpower mobility and job security. The free labor market cannot by itself serve as the mechanism for realizing these goals. Employment security and not segmentation of the work force should be the objective of joint policy making.